Phytochemical Characterization and In Vitro Antioxidant Activity of Murraya Koenigii Leaf Extract - Nafi'ah, Radifatun; Febrinasari, Ratih Puspita; Sari, Yulia (Journal of Health and Nutrition Research, 2025)
Murraya koenigii (curry leaf) is a tropical plant known for its diverse phytochemical content and potent antioxidant activity. However, limited studies have provided comprehensive quantitative data on its bioactive compounds, especially from Indonesian varieties. This study aimed to quantitatively analyze flavonoid, saponin, and tannin content in young and mature curry leaves and evaluate their in vitro antioxidant activity using the DPPH assay. An experimental design was conducted from January to March 2025. Ethanolic extracts of young and mature M. koenigii leaves from Aceh were prepared via maceration. Phytochemical quantification was performed using spectrophotometric methods, and antioxidant capacity was assessed using the DPPH radical scavenging assay with IC₅₀ determination. Young leaves showed higher levels of total flavonoids (0.19%), saponins (3.34%), and tannins (5.77%) compared to mature leaves (0.13%, 2.53%, and 4.58%, respectively). However, mature leaf extract exhibited stronger antioxidant activity with an IC₅₀ value of 46.77 μg/mL (very strong category), while young leaves showed 53.14 μg/mL (strong category). This suggests that antioxidant efficacy is influenced more by compound maturity and synergistic effects than total concentration. Mature M. koenigii leaves have superior antioxidant potential despite lower phytochemical concentrations, highlighting the importance of compound quality and interactions between compounds.